Uranium isotopes as radioactive pollutants in groundwaters of the Morro do Ferro thorium deposit, Brazil - Bonotto, D. M. (IWA Publishing, 1991)
Groundwater and surface water samples were collected at Morro do Ferro, a thorium and rare earth deposit located on the Pocos de Caldas Plateau, Minas Gerais State, Brazil, to evaluate if the mechanisms related to the migration of 238U and 234U isotopes can generate concentrations greater than the gross-alpha activity contaminant limit. The 238U content range was 0.003-0.24pCi/l and the 234U content range was 0.004-0.25pCi/l, showing that the studied hydrologic environment doesn't indicate pollution by radioactivity due to these nuclides. However, 226Ra and 228Ra isotopes can be considered as radioactive pollutants in groundwaters but not in surface waters of the Morro do Ferro.

Groundwater and surface water samples were collected at Morro do Ferro, a thorium and rare earth deposit located on the Pocos de Caldas Plateau, Minas Gerais State, Brazil, to evaluate if the mechanisms related to the migration of 238U and 234U isotopes can generate concentrations greater than the gross alpha activity contaminant limit. The 234U content range was 0.004-0.25 pCi/1, and the 234U content range was 0.004-0.25 pCi/l, showing that the studied hydrologic environment doesn't indicate pollution by radioactivity due to these nuclides. However, 226Ra and 220Ra isotopes can be considered as radioactive pollutants in groundwaters but not in surface waters of the Morro do Ferro.